2019
DOI: 10.1177/1043454219891989
|View full text |Cite
|
Sign up to set email alerts
|

The Nurse’s Role in Prognosis-Related Communication in Pediatric Oncology Nursing Practice

Abstract: The experiences of pediatric oncology nurses with prognosis-related communication (PRC) remain largely unknown. The purpose of this article is to report results of focus groups wherein 15 pediatric oncology nurses from three Midwestern pediatric cancer programs provided descriptions of PRC and how they experience PRC within their daily practice. Data from focus groups were analyzed via an interpretive descriptive approach, which resulted in three themes: (1) nurses’ operational definition of PRC, (2) nurses’ r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 35 publications
0
13
0
10
Order By: Relevance
“…Individual‐level factors were identified in 100 studies, related to individual characteristics of the clinician, parents, or patients, or characteristics of the clinician–patient–family interaction. Clinician characteristics and behaviors that were examined as potential influences on communication included: complexity of language and terminology, 33–38 pacing of information, 39–43 demonstrations of competence, 42,44–48 level of comfort or training related to sensitive topics, 4,42,49–62 perceived importance of certain topics, 51,61–68 concerns about harms of discussing certain topics, 69–72 exploration of family's values and taking them seriously, 38,40,41,73–77 and demonstrations of empathy and caring 7,38,39,78,79 . Some studies identified a tension between a desire to show empathy and a need to create appropriate emotional distance to allow for effective communication and decision‐making 57,64,70,80,81 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual‐level factors were identified in 100 studies, related to individual characteristics of the clinician, parents, or patients, or characteristics of the clinician–patient–family interaction. Clinician characteristics and behaviors that were examined as potential influences on communication included: complexity of language and terminology, 33–38 pacing of information, 39–43 demonstrations of competence, 42,44–48 level of comfort or training related to sensitive topics, 4,42,49–62 perceived importance of certain topics, 51,61–68 concerns about harms of discussing certain topics, 69–72 exploration of family's values and taking them seriously, 38,40,41,73–77 and demonstrations of empathy and caring 7,38,39,78,79 . Some studies identified a tension between a desire to show empathy and a need to create appropriate emotional distance to allow for effective communication and decision‐making 57,64,70,80,81 …”
Section: Resultsmentioning
confidence: 99%
“…Hierarchy within teams and perceived authority seemed to affect clinicians’ communication practices, especially related to prognostic discussions and introduction of palliative care 16,55,70 . Clear delineation and delegation of this authority seemed to facilitate communication 16,42,55,60,124 . Two studies described negative family experiences related to receiving contradictory information from different team members 16,45 .…”
Section: Resultsmentioning
confidence: 99%
“…• Transmite información clara sobre la atención de la salud a grupos étnicamente diversos a través de diferentes medios (68,70,72,77,78).…”
Section: Habilidadesunclassified
“…• Demuestra la capacidad de incorporar estrategias de comunicación al tratar información específica sobre el cáncer con los pacientes y sus familias a fin de mejorar la alfabetización en salud y mejorar el acceso, la comprensión y el uso de la información sobre salud (65,78).…”
Section: Habilidadesunclassified
See 1 more Smart Citation